2015
DOI: 10.1039/c5ra09406b
|View full text |Cite
|
Sign up to set email alerts
|

In vivo reversal of general anesthesia by cucurbit[7]uril with zebrafish models

Abstract: A general anesthetic is a drug that brings about a reversible loss of consciousness, during a surgical or therapeutic procedure to render the patient free of pain and anxiety. However, the effect of anesthetics may linger far beyond the necessary time required and induce adverse effects. In addition, many surgical patients need to recover to a conscious state that allows them to make important decisions soon after their surgery. Unfortunately, there are currently no clinically-available anti-dotes to reverse t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
48
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 45 publications
1
48
0
Order By: Relevance
“…1b,3 In addition, CB[n]-type receptors exhibit good biocompatibility, and have therefore been used to formulate, protect, and deliver drugs, as reversal agents to mitigate drug (side) effects, and for various sensing applications. 4 Earlier, the excellent recognition properties of CB[n] were combined with nanoparticles for biological and material applications. 5 For example, the Zink, Stoddart, and Yang groups have created mesoporous silica nanoparticles that are gated by host-guest recognition processes.…”
Section: Introductionmentioning
confidence: 99%
“…1b,3 In addition, CB[n]-type receptors exhibit good biocompatibility, and have therefore been used to formulate, protect, and deliver drugs, as reversal agents to mitigate drug (side) effects, and for various sensing applications. 4 Earlier, the excellent recognition properties of CB[n] were combined with nanoparticles for biological and material applications. 5 For example, the Zink, Stoddart, and Yang groups have created mesoporous silica nanoparticles that are gated by host-guest recognition processes.…”
Section: Introductionmentioning
confidence: 99%
“…27,31,32 Given their excellent biocompatibility, other recent efforts have sought to use CB[n]-type receptors to enhance drug solubility, for imaging applications, and as a drug reversal agent. 31,33 Pioneering work in this area was performed by Yang, Zink, and Stoddart based on mesoporous silica nanoparticles that are gated by host•guest recognition processes. 23,34 In this paper, we decorate the external surface of Fujita-type Pd 12 L 24 metal organic polyhedra (MOP) with MV ligands, explore their non-covalent functionalization with CB[n], and demonstrate their ability to deliver doxorubicin to cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…19 Very recently, our group reported the ability of CB [7] to reverse the effects of general anesthesia induced by tricaine in vivo. 11 It has also been shown that the myotoxicity and cardiotoxicity of cisplatin was significantly reduced after this drug had been encapsulated by CB [7]. 20 CB [7] was also found to inhibit amyloid fibrillation, thus potentially finding therapeutic applications to prevent or treat amyloidosis.…”
mentioning
confidence: 99%